David Bergé - a walk in high resolution - Bergé, David 1983- (Jap Sam Books, 2020)
Since 2008, Belgian artist David Bergé has been making Walk Pieces, during which he guides participants in silence along a precise trajectory and within a precise timeframe through textures and infrastructures that comprise the city. Walking together resonates with the phenomenological minutiae of street life and for the entire duration of the Walk Piece, participants refrain from verbal exchange and picture taking. Participating in a Walk Piece and/or your personal experience of reading this book are the only valid materializations of David Bergé's ephemeral works. 'A Walk in High Resolution' deals with corporeality, sleeping, awakening, and walking through the interiors and fissures of urban infrastructures. Almost touching neighboring bodies, reliving experiences in cities by being absorbed in space that is at once personal, reflective, consumptive, and the other, we walk through cities
Colophon: This book was first presented in the framework of "A Walk in High Resolution", an exhibition at Out of Sight, a venue for contemporary art in Antwerp, curated by Dušica Dražic. - Genaue Ausstellungsdaten ermittelt: 23 November - 22 December 2019, Out of Sight, Antwerp
Keywords: Bergé, David -- 1983-; Fotografie; Ausstellungskatalog -- Out of Sight -- 23.11.2019-22.12.2019 -- Antwerpen